1998
DOI: 10.1029/1998gl900090
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal variation of auroral ion beams

Abstract: Abstract. We present observations of a seasonal variation in the occurrence frequency of upflowing ions beams near 1 RE altitude in the 1800-2400 local time sector. These observations were obtained from the Toroidal Imaging MassAngle Spectrograph (TIMAS) instrument during POLAR satellite perigee passes from March 1996 to September 1997. We show that the observed variation is most simply interpreted as a variation in the magnitude of the auroral acceleration process responsible for creating upflowing ion beams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 15 publications
7
58
1
Order By: Relevance
“…Comparing radial distance bins below 2.5 R E for high K p conditions, the occurrence frequency in darkness is 0.05, which is 2.5 times higher than in sunlit conditions in the evening sector (18-22 MLT). Overall, this is in agreement with a previous study where a ratio of ∼3 was found in the occurrence frequency in darkness versus sunlit beams (Collin et al, 1998), although the beam selection criteria and thus the absolute occurrence frequencies are different in the two studies. It is also seen that in the evening sector between 2.5 and 3.5 R E the occurrence rate of ion beams is higher during darkness than during sunlit conditions, although the difference is not as large as below 2.5 R E .…”
Section: Mlt and Solar Illuminationsupporting
confidence: 82%
See 1 more Smart Citation
“…Comparing radial distance bins below 2.5 R E for high K p conditions, the occurrence frequency in darkness is 0.05, which is 2.5 times higher than in sunlit conditions in the evening sector (18-22 MLT). Overall, this is in agreement with a previous study where a ratio of ∼3 was found in the occurrence frequency in darkness versus sunlit beams (Collin et al, 1998), although the beam selection criteria and thus the absolute occurrence frequencies are different in the two studies. It is also seen that in the evening sector between 2.5 and 3.5 R E the occurrence rate of ion beams is higher during darkness than during sunlit conditions, although the difference is not as large as below 2.5 R E .…”
Section: Mlt and Solar Illuminationsupporting
confidence: 82%
“…8 of Kondo et al (1990)), it was found that the ion fluxes increase as a function of K p , which probably reflects the general increase in auroral processes with K p . Using one year of TIMAS data it has also been found that ion beams below 10 000 km occur ∼3 times more often during wintertime than during summertime (Collin et al, 1998). This probably reflects the fact that during summertime, potential structures and their associated ion beams often reside at higher altitude, because of higher underlying ionospheric plasma density and thus were more often beyond the upper altitude limit of this study.…”
Section: Introductionmentioning
confidence: 89%
“…As the electrons are accelerated by field-aligned electric field, protons are decelerated or accelerated upward. The observation of the seasonal variation of the upward ion beam was described in Collin et al (1998). Observations with the TIMAS instrument on board the POLAR satellite are similar to the seasonal variations of the intense electron aurora and are in agreement with the mechanism.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, it is possible that some ion heating on the nightside occurs above Freja altitudes in sunlit conditions. In a study of POLAR data from 5000 km altitude ion-beams were found predominantly during winter but transversely heated ion distributions were found with equal probabilities during summer and winter [Collin et al, 1998]. We note that distributions heated mainly at Freja altitudes would have been detected as field aligned beams in this investigation.…”
Section: Discussionmentioning
confidence: 88%